Impact of opioid-induced constipation on opioid substitution therapy management: the patient perspective - Fabio Lugoboni; Genevieve Hall; Vivek Banerji (BioExcel Publishing Ltd, 2021)
Background: Although opioid-induced bowel dysfunction is a well-known and frequent adverse event correlated with opioids, it is scarcely investigated in patients on opioid substitution treatment (OST) and no standard of care is currently available for this population. We aimed to explore the opinion of patients on the impact of constipation on the management of OST and quality of life (QoL). Methods: We performed a survey that was directed to opioid-dependent patients treated with OST and followed-up in a Service for Addiction Treatment in Italy. The questionnaire included questions about sociodemographic characteristics, the experience of constipation, general QoL, OST management, interference of opioid-induced constipation (OIC) with opioid management, the experience of OIC treatment in the health system, and risk factors for constipation. Results: Constipation at the moment of the survey (n=105) was reported by 81% of patients and was the most frequent adverse event of OST; 73% of respondents reported at least one severe or very severe symptom of constipation in the last 2 weeks. OIC was reported to hinder adherence to OST by 33% of respondents and 38% of them felt that control of craving had been more difficult since initiation of constipation. Overall, 34% of patients interfered with their OST by changing the schedule on their own in an attempt to improve constipation. Patients were proactive in looking for a solution for constipation but reported poor help from the healthcare system. Conclusion: Our patient-based survey suggests that careful and efficient management of constipation could increase adherence to OST and improve patient satisfaction and QoL.